2019
DOI: 10.28945/4252
|View full text |Cite
|
Sign up to set email alerts
|

Ranking of Accounting Doctoral Programs Based on Student Ratings in Ratemyprofessors.com and the Effect of Formal Teaching Training on the Rankings

Abstract: Aim/Purpose: Although there are calls for better teaching training for accounting doctoral students, there are limited research findings on rankings of accounting doctoral programs based on the teaching effectiveness of their graduates. Background: There are two research objectives of this study. First, we rank the US accounting doctoral programs based on the student perceptions of the teaching effectiveness of their graduates using student ratings in ratemyprofessors.com. Second, we examine whether the ranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 34 publications
0
12
0
3
Order By: Relevance
“…Supporting the need for training doctoral students to teach, Chan et al (2019) found that doctoral instructors from programs requiring formal teaching training were more highly rated by undergraduates taking accounting courses. Madhavaram and Laverie wrote in 2010, "PC [pedagogical competence] can be traced back to doctoral programs" and called for marketing doctoral programs to "evolve from a strict research focus to a research and teaching focus," suggesting that doctoral students complete a year-long seminar course requiring participants to develop lectures, pedagogical approaches, learning goals and outcomes, and assessment techniques.…”
Section: Preparing Doctoral Students To Teachmentioning
confidence: 99%
“…Supporting the need for training doctoral students to teach, Chan et al (2019) found that doctoral instructors from programs requiring formal teaching training were more highly rated by undergraduates taking accounting courses. Madhavaram and Laverie wrote in 2010, "PC [pedagogical competence] can be traced back to doctoral programs" and called for marketing doctoral programs to "evolve from a strict research focus to a research and teaching focus," suggesting that doctoral students complete a year-long seminar course requiring participants to develop lectures, pedagogical approaches, learning goals and outcomes, and assessment techniques.…”
Section: Preparing Doctoral Students To Teachmentioning
confidence: 99%
“…Like many other educational programmes, Higher Education is a period of socialisation in preparation for a prospective career, including academia (Austin et al 2009). As an academic, one is expected to engage in teaching, research, and service (community or leadership) with administrative duties across all categories (Khan & Siriwardhane 2021;Chan et al 2019;Bexley 2013;Martin 1984). However, for decades, the focus of doctoral studies in many research institutions has been on research and disciplinary content expertise to the detriment of teaching (Bishop-Monroe et al 2021;Bonner et al 2020;Barney 2019;Marx et al 2016;Boman 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As discussões relacionadas à temática da formação e da preparação docente têm sido ampliadas para cursos cuja formação inicial não trazem bases didático--pedagógicas e onde há pouca ou nenhuma formação docente de professores de nível superior, como é o caso dos bacharelados, os quais incluem os cursos de Administração e Ciências Contábeis (POSTAREFF; LINDBLOM-YLANNE; NEVGI, 2007;ABDULLAH et al, 2016;LOURENÇO;NARCISO, 2016;CHAN et al, 2019). Nestas áreas, a formação pedagógica apresenta-se deficitária, necessitando ser desenvolvida a partir de outras fontes de conhecimento que levem à formação e ao desenvolvimento da identidade do profissional docente (LOURENÇO; LIMA; NARCISO, 2016; VAN LANKVELD et al, 2017).…”
unclassified
“…No entanto, parece que os cursos de mestrado e doutorado não têm se constituído como espaço formativo para o desenvolvimento dessas atividades de ensino e aprendizagem. Os achados de Andere e Araujo (2008), Miranda (2010), Lapini (2012), Slomski et al (2013, Patrus e Lima (2014), Abdullah et al (2016), Nganga et al (2016), Araujo (2017), Silva e Ramos (2017), Lima et al (2019) e Chan et al (2019) reforçam que os programas de pós-graduação em Contabilidade e Administração 110 têm apresentado maior preocupação com a formação de pesquisadores em detrimento da formação de docentes, ainda que esteja previsto como um dos objetivos pedagógicos dos cursos.…”
unclassified
See 1 more Smart Citation